Rooted in Resilience: Climate Change and Mental Health Narratives of Makgobistad’s Emerging Adults - Vukile Ncango; Caroll Hermann; Eugene Lee Davids (South African Journal of Psychology, 2026)
The psychological consequences of climate change remain understudied, particularly among emerging adults in marginalised rural settings. This study explored the impact of climate change on the mental health of emerging adults in Makgobistad, a semi-arid village in the North West Province of South Africa. The study included eight participants aged 18 to 25 years who shared their experiences through photovoice and semi-structured interviews. The data were analysed using thematic analysis. Contributing to a growing body of evidence, the data tell a story through three major themes: (a) the impact of climate change on daily life, (b) eco-anxiety and emotional distress, and (c) fostering ecological coping. The findings further highlight how environmental uncertainty, food insecurity, and socioeconomic stress intersect to amplify psychological vulnerability among emerging adults in Makgobistad. This study centres lived, situated knowledge, aligning with critiques of previous research that overlook localised, rural impacts. The findings have implications for the delivery of psychological services, climate adaptation policies, and community-based mental health interventions aimed at youth resilience. The data underscore the urgent need for contextually grounded and climate-informed mental health strategies in rural South Africa and similar global settings.